Clinical results of proton therapy reirradiation for recurrent nasopharyngeal carcinoma. (2nd September 2019) - Dionisi, F.; Croci, S.; Giacomelli, I.; Cianchetti, M.; Caldara, A.; Bertolin, M.; Vanoni, V.; Pertile, R.; Widesott, L.; Farace, P.; Schwarz, M.; Amichetti, M.
Abstract: Background and purpose: Recurrent nasopharyngeal carcinoma (NPC) has limited curative treatment options. Reirradiation is the only potential definitive treatment in advanced stages at a cost of substantial severe and often life-threatening toxicity. Proton therapy (PT) reduces irradiated volume compared with X-ray radiotherapy and could be advantageous in terms of safety and efficacy in a population of heavily pretreated patients. We report the retrospective results of PT reirradiation in recurrent NPC patients treated at our Institution Methods: All recurrent NPC patients treated since the beginning of clinical activity entered the present analysis. Clinical target volume consisted of Gross Tumor volume plus a patient-specific margin depending on disease behavior, tumor location, proximity of organs at risk, previous radiation dose. No elective nodal irradiation was performed. Active scanning technique with the use of Single Field Optimization (SFO) or Multifield Optimization (MFO) was adopted. Cumulative X-ray -PT doses were calculated for all patients using a dose accumulation tool since 2016. Treatment toxicity was retrospectively collected. Results: Between February 2015, and October 2018, 17 recurrent NPC patients were treated. Median follow-up (FUP) was 10 months (range 2–41). Median PT reirradiation dose was 60 Gy RBE (range 30.6–66). The majority of patients (53%) underwent concomitant chemotherapy. Acute toxicity was low with no ≥ G3 adverse events. Late events ≥ G3 occurred in 23.5% of patients. Most frequent late toxicity was hearing impairment (17, 6%). G2 soft tissue necrosis occurred in two patients. Fatal bleeding of uncertain cause (either tumor recurrence or G5 carotid blowout) occurred in one patient. Kaplan–Meier 18 months Overall Survival (OS) and Local control (LC) rates were 54.4% and 66.6%, respectively. Conclusions: Our initial results with the use of modern PT for reirradiation of recurrent NPC patients are encouraging. Favorable LC and OS rates were obtained at the cost of acceptable severe late toxicity.